Association of serum lipids with levels of leptin in hemodialysis patients - Rafieian-Kopaei, Mahmoud (J Nephropharmacol, 2013)
To consider the correlation of serum leptin with dyslipidemia in hemodialysis patients. For maintenance hemodialysis patients levels of serum, lipid profiles and serum leptin were measured. Stable hemodialysis patients enrolled to the study. In all patients (36) a near significant,inverse correlation of serum leptin with serum LDL-C was seen. In male hemodialysis group a near significant positive correlation of serum leptin with serum triglyceride level was seen. The association of leptin with cholestrol and triglycerid levels could show the impact of leptin on nutrition status of hemodialysis patients.